Affective and autonomic response to dynamic rhythmic entrainment: mechanisms of a specific music therapy factor - Kim, Sungeun; Gäbel, Christine; Aguilar-Raab, Corina; Warth, Marco (The arts in psychotherapy, 2018)
Dynamic rhythmic entrainment, that is the bi-directional synchronization between an internal oscillator and an external musical beat, is frequently used in music therapy to promote psychophysiological relaxation and well-being. However, little is understood about the nature of this mechanism and its link to affective judgments. The objective of this study was to examine specific cardiovascular and affective effects of live music matched with the listener’s heart beat, with the tempo gradually decreased to assess the relaxation effect. Thirty apparently healthy students were randomized to either the experimental (EG) or the control group (CG). After a brief mental stress task, both groups listened to a live music therapy relaxation technique. While a biofeedback device was utilized to enable real-time synchronization of relaxing music to the listener’s pulse in the EG, the tempo in the CG was fixed to 70 beats per minute. Self-ratings of stress and well-being, as well as autonomic measures of cardiovascular reactivity were assessed. The entrained-tempo condition led to a significantly stronger increase in peripheral blood flow (p< .01) and subjective well-being (p= .036). No between-group differences were observed for changes in pulse rate and self-rated stress level (both p> .05). We conclude that rhythmic entrainment may promote a psychophysiological relaxation response. The decrease in sympathetic arousal may have led to more favorable affective self-ratings via an interoceptive feedback process, but more research is needed to clarify the direction of effects.
Gesehen am 21.10.2019